Caspase‐cleaved keratin‐18 fragments increase during alcohol withdrawal and predict liver‐related death in patients with alcoholic liver disease. Issue 1 (9th May 2017) - Mueller, Sebastian; Nahon, Pierre; Rausch, Vanessa; Peccerella, Tessa; Silva, Ines; Yagmur, Eray; Straub, Beate K.; Lackner, Carolin; Seitz, Helmut K.; Rufat, Pierre; Sutton, Angela; Bantel, Heike; et al.
Abstract : Noninvasive assessment of disease activity in patients with nonalcoholic fatty liver disease (NAFLD) and alcoholic liver disease (ALD) is still unsettled, but essential for the evaluation of disease progression. We here studied the association of total (M65) and caspase‐cleaved (M30) serum keratin‐18 fragments (n = 204) with histological parameters (n = 106) in heavy drinkers primarily admitted for alcohol withdrawal before and after alcohol detoxification. An age‐, sex‐, and fibrosis‐stage matched NAFLD cohort (n = 30) was used for comparison. The prognostic value of M30 and M65 levels were assessed in an additional prospectively followed‐up cohort of 230 patients with alcoholic cirrhosis (AC) using competing risk analyses. Among the histological parameters, both M30/65 correlated significantly and better than any other serum marker with apoptosis and liver damage, such as ballooning (r = 0.65; P < 0.001), followed by lobular inflammation (0.48; P < 0.001), steatosis (0.46; P < 0.001), but less with fibrosis (0.24; P < 0.001). Area under the receiver operating characteristics curves to detect ballooning, steatosis, or steatohepatitis (SH) were slightly better for M30 ( P < 0.005). Optimal M30 cut‐off values for mild and severe ballooning were 330 and 420 U/L, and 290 and 330 U/L for SH grades 1 and 2. No significant differences of M30/65 were found between the matched NAFLD and ALD cohort. In contrast to aspartate‐amino‐transferase and M65, M30 levels increased significantly from 391 to 518 U/L during alcohol detoxification. Moreover, levels of M30 and M65 predicted non–hepatocellular carcinoma liver‐related mortality in patients with AC during a mean observation interval of 67.2 months. Conclusion : Our data suggest M30 as highly specific marker of liver apoptosis both in ALD and NAFLD. In addition, hepatocellular apoptosis, as determined by M30 levels, occurs during alcohol withdrawal, and survival data point toward a novel underestimated role of apoptosis in patients with ALD. (Hepatology 2017;66:96–107).